Coupling coordination analysis and factors of “Urban renewal-ecological resilience-water resilience” in arid zones - Sun, Yu; Li, Xinwu (Frontiers in Environmental Science, 2025)
Promoting the coordinated development of urban renewal, ecological resilience, and water resilience in Xinjiang is the key to promoting sustainable urban development. The paper applies the comprehensive evaluation method, modified CCD model, kernel density estimation, traditional and spatial Markov chain, spatial econometric model, and GTWR, to analyze the distribution characteristics, spatial evolution, and factors of coordinated level of urban renewal-ecological resilience-water resilience in the 14 prefectures in Xinjiang from 2010–2021. The results show that: (1) The development levels of Xinjiang’s urban renewal, ecological resilience, and water resilience show an overall upward trend, exhibiting qualities of “high in the north and low in the South” in space. (2) Urban renewal-ecological resilience-water resilience coordination level across Xinjiang prefectures show a polarizing trend, with spatial core areas of nuclear density shrinking, but coordination levels increasing overall. In the short term, the transfer of the coordination level in Xinjiang has higher stability; after the introduction of spatial geography, the coordination level shifts to a higher level with a higher probability. (3) Urban population density, infrastructure level, total environmental investment, per capita GDP, and fiscal technology expenditure all support the enhancement of the coordination level. The infrastructure level and overall environmental investment have notable negative spatial spillover effects, and the impact of the five components has regional differentiation characteristics. This study provides a theoretical and empirical basis for Xinjiang to achieve sustainable urban development according to local conditions.